Optimization of Formula Fast Disintegrating Tablet (FDT) Antacids with Simplex Lattice Design Method - Siswanto, Agus; Himawanti, Nanda Puspita; Khasanah, Fitria Nurrul (Jurnal Kefarmasian Indonesia, 2024)
Antacids are compounds that can neutralize stomach acid. Antacid preparations on the market are generally in the form of powders, suspensions, and chewable tablets. However, this dosage form is considered less practical, so an alternative dosage form is needed. FDT antacids are one of the quick-dissolving tablet strategies to neutralize stomach acid. The combination of Avicel PH 101 with a wicking mechanism and Sodium Starch Glycolate (SSG) with swelling action is expected to increase the effectiveness of the super disintegrant. The simplex lattice design method (Design Expert 7.1.5) was used to optimize the super disintegrant of SSG (A) and Avicel PH 101 (B). Tablets were prepared using the wet granulation method in an 8-run formula. The optimum formula for FDT antacids was determined by disintegration time and acid neutralization capacity parameters. The results showed that increasing Avicel PH 101 in combination with SSG decreased the disintegration time and increased the value of the acid neutralization capacity of the FDT antacid. Based on the optimization of the numerical method, the optimum composition of the FDT antacid formula was obtained with a combination of 38 % SSG and 101 % Avicel PH 101.